The Strategi Pembelajaran Musik Band melalui Pendekatan Ragam Metode: Indonesia - Sembiring, Piter; Nurfalah, Asep Rizwan (Program Studi Pendidikan Musik, 2025)
This study explores instructional strategies in band music education through a diverse methodological approach aimed at enhancing students’ musical competence. Responding to the demands of 21st-century learning, this research emphasizes the need for adaptive, student-centered strategies that integrate various methods to support both individual and group musical development. Using a qualitative descriptive approach with library research as the primary method, the study examines the implementation of demonstration, imitation, side-by-side guidance, and peer tutoring within band music instruction. The integration of these methods fosters a collaborative and interactive learning environment that enhances students' technical skills, creativity, autonomy, and musical expression across multiple instruments including guitar, bass, drums, keyboard, and vocals. This research contributes conceptually and practically by offering an effective pedagogical framework for music educators to design instructional strategies that align with students’ diverse learning styles. The findings underscore the importance of methodological variation in creating meaningful, inclusive, and dynamic band music learning experiences.